Part of Speech Mastery of Thai Students of Xavier Learning Community, Thailand - Sumit Choemue; Barli Bram (VELES Voices of English Language Education Society, 2020)
This paper investigated the Thai students’ mastery of parts of speech in English. It is urgent to conduct this study because it would explore the students’ difficulties in identifying parts of speech when producing grammatical sentences and then assist them in tackling the language challenges. The data consisted of 30 written reflections produced by students belonging to two classes and were collected from all of the 30 students of batch 2018 pursuing their Bachelor of Arts degrees at Xavier Learning Community (XLC) in Chiang Rai, Thailand. This error analysis study examined the (mis)use of the four main parts of speech or syntactic categories, namely adjectives, adverbs, nouns and verbs in written reflections of XLC students. Results showed that in general the students still faced challenges in recognizing and using parts of speech grammatically in writing reflections. The highest number of mistakes involved adjectives, namely 32 times (46.37%), and consecutively followed by nouns, 18 (26.08%), verbs, 15 (21.73%) and adverbs, 4 (5.79%).